+0  
 
0
266
1
avatar

3 lg x= lg10

Guest May 17, 2017
 #1
avatar+17745 
0

Assuming that 'lg' means 'log' (either base 10 or base 2):

3 lg( x )  =  lg( x3 )

So, the equation becomes  3 lg( x )  =  lg( 10 )     --->     lg( x3 )  =  lg( 10 )     --->     x3  =  10

                                                                                                                         --->       x  =  cuberoot( 10 )

geno3141  May 17, 2017

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.